An adaptive grid algorithm for self-consistent k·p Schrodinger and Poisson equations in UTB InSb-based pMOSFETs - Pengying Chang; Xiaoyan Liu; Lang Zeng; Kangliang Wei; Gang Du (2014 International Workshop on Computational Electronics (IWCE), 2014)
Hole mobility in ultra-thin body (UTB) InSb-OI devices is calculated by a microscopic approach. An adaptive grid algorithm is employed to discretize 2-D k space. The accurate valence band structures are obtained via solving the 6-band k·p Schrödinger and Poisson equations self-consistently. Hole mobility is computed using the Kubo-Greenwood formalism accounting for nonpolar acoustic and optical phonons, polar optical phonons, and surface roughness scattering mechanisms.